1995
DOI: 10.1074/jbc.270.32.18723
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Carrier Protein-2 Is Involved in Cholesterol Transfer from the Endoplasmic Reticulum to the Plasma Membrane in Human Fibroblasts

Abstract: The cellular mechanism of cholesterol transport from the endoplasmic reticulum to the plasma membrane is currently unknown. To assess the possibility that sterol carrier protein-2 (SCP-2) is involved in this transport, we studied the time course of newly synthesized cholesterol incorporation in the plasma membrane of normal and SCP-2-deficient (Zellweger syndrome) human fibroblasts. Cholesterol transfer was rapid, cytoskeleton-independent, and Golgi-independent in normal cells, but it was slower, cytoskeleton-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 25 publications
8
84
0
Order By: Relevance
“…The physiological impact of cholesterol binding proteins such as SCP-2 and L-FABP on cholesterol uptake, esterification, and excretion into bile was confirmed by studies with SCP-2 transgenic (i.e. overexpressing or antisense cDNA treated) mice and rats (177-179) Studies with radiolabeled cholesterol were consistent with many of the findings shown with the fluorescent DHE and other sterols in cultured cells (43,45,172,(190)(191)(192)(193)(194)(195)(196)(197). In one study, it was shown that overexpression of L-FABP in L-cell fibroblasts enhanced the transfer or radiolabled cholesterol from the plasma membrane to the endoplasmic reticulum for esterification (194).…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 78%
“…The physiological impact of cholesterol binding proteins such as SCP-2 and L-FABP on cholesterol uptake, esterification, and excretion into bile was confirmed by studies with SCP-2 transgenic (i.e. overexpressing or antisense cDNA treated) mice and rats (177-179) Studies with radiolabeled cholesterol were consistent with many of the findings shown with the fluorescent DHE and other sterols in cultured cells (43,45,172,(190)(191)(192)(193)(194)(195)(196)(197). In one study, it was shown that overexpression of L-FABP in L-cell fibroblasts enhanced the transfer or radiolabled cholesterol from the plasma membrane to the endoplasmic reticulum for esterification (194).…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 78%
“…Transport of de novo-synthesized cholesterol to the plasma membrane is energy-and temperature-dependent and thought to be mediated via lipid-rich transport intermediates (11,(30)(31)(32). Inhibitors of glycoprotein export, such as BFA, result in only modest reductions in cholesterol export, suggesting that the majority of cholesterol transported to the plasma membrane bypasses the Golgi apparatus in BFA-treated cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Another protein, sterol carrier protein x/2 (SCPx/2), has also been implicated in the initial rapid transport of cellular cholesterol to the plasma membrane. 50 The impaired HDL-and apoA-I-mediated lipid efflux in FHD fibroblasts does not appear to be related to a defective HDL interaction with cell surface binding proteins. We found that binding of HDL 3 at 4°C to cholesterol-loaded FHD fibroblasts was not significantly different from HDL 3 binding to normal cells.…”
Section: Discussionmentioning
confidence: 99%